Surface-enhanced Raman scattering measurement from a lipid bilayer encapsulating a single decahedral nanoparticle mediated by an optical trap - Wright, Amanda J.; Richens, Joanna L.; Bramble, J.P.; Cathcart, N.; Kitaev, V.; O'Shea, Paul; Hudson, A.J. (Royal Society of Chemistry, 2016)
We present a new technique for the study of model membranes on the length-scale of a single nanosized liposome. Silver decahedral nanoparticles have been encapsulated by a model unilamellar lipid bilayer creating nano-sized lipid vesicles. The metal core has two roles (i) increasing the polarizability of vesicles, enabling a single vesicle to be isolated and confined in an optical trap, and (ii) enhancing Raman scattering from the bilayer, via the high surface-plasmon field at the sharp vertices of the decahedral particles. Combined this has allowed us to measure a Raman fingerprint from a single vesicle of 50 nmdiameter, containing just ∼104 lipid molecules in a bilayer membrane over a surface area of <0.01 µm2, equivalent to a volume of approximately 1 zepto-litre. Raman scattering is a weak and inefficient process and previous studies have required either a substantially larger bilayer area in order to obtain a detectable signal, or the tagging of lipid molecules with a chromophore to provide an indirect probe of the bilayer. Our approach is fully label-free and bio-compatible and, in the future, it will enable much more localized studies of the heterogeneous structure of lipid bilayers and of membrane-bound components than is currently possible.